2019
DOI: 10.19173/irrodl.v20i2.4018
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Mapping Study of Academic Engagement in MOOC

Abstract: MOOCs are presented as an affordable and easily accessible modality that offers the opportunity to democratize education in our time; however, this convenience training favors a low completion rate of the participants. Faced with this situation, scholars have suggested that it is necessary to deepen the construct of academic engagement, a concept that has been addressed in the study of face-to-face training, to better understand how students participate in this educational modality. This article systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…As both the above reviews analyzed 38 articles within a narrow time frame of about 3–4 years, there was a need to extend current empirical knowledge to explore more findings. Davis et al ( 2018 ) investigated 126 MOOC studies published between 2009 and 2017 from an active learning perspective and found that the three most effective active learning strategies were cooperative learning, simulations and gaming, and interactive multimedia, and Guajardo Leal et al ( 2019 ) focused on MOOC learning engagement and reviewed 176 articles published from 2015 to 2018, finding that most related articles were from the United States, Australia, and the United Kingdom and most had employed qualitative exploratory methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As both the above reviews analyzed 38 articles within a narrow time frame of about 3–4 years, there was a need to extend current empirical knowledge to explore more findings. Davis et al ( 2018 ) investigated 126 MOOC studies published between 2009 and 2017 from an active learning perspective and found that the three most effective active learning strategies were cooperative learning, simulations and gaming, and interactive multimedia, and Guajardo Leal et al ( 2019 ) focused on MOOC learning engagement and reviewed 176 articles published from 2015 to 2018, finding that most related articles were from the United States, Australia, and the United Kingdom and most had employed qualitative exploratory methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In response to the general objective of this research, it was found that personal factors [3,4], family factors [8][9][10], social factors [14], instructional design factors [17,18] and labor factors [29] influence both the decision to take a MOOC (expectation-value) and, to a certain extent, engagement in the training program-measured by completion rates-as noted in the review of the state of the art. However, not all factors do so in the same way.…”
Section: Discussionmentioning
confidence: 96%
“…Familiar factors also have a relation to the commitment of MOOC participants. Several studies have developed instruments that consider the background and demographic data as substantial [8] and literature reviews that highlight the importance of building academic commitment and self-regulation to be effective [9,10]. Self-efficacy takes into account student characteristics to understand why some students do not complete these courses [11], where the theory of self-determination touches on issues and sections such as participants' autonomy, competence, and affinity, and based on this, studies and analyzes the background of MOOC participants [12].…”
Section: Introductionmentioning
confidence: 99%
“…Henrie, Halverson, and Graham's [48] review examined the current approaches to measuring student engagement in technology-mediated learning, finding that quantitative self-report, qualitative measures, quantitative observational measures, and physiological sensors have been used. Similarly, Guajardo-Leal, Navarro-Corona, and González [45] systematically mapped academic engagement in MOOCs to identify and delineate the construct of academic engagement in MOOCs. Their results show the methodological perspectives, designs, and approaches and the types of instruments used, as well as emerging thematic trends in the study of academic engagement in MOOCs.…”
Section: Learners' Engagement In Moocsmentioning
confidence: 99%